ANALISIS FAKTOR-FAKTOR KESALAHAN DALAM MENULIS TEKS PUISI CITA-CITAKU MATA PELAJARAN BAHASA INDONESIA KELAS III DI SD GMIT PITUNGBANG - Hana M. Dael; Antonius A. Saetban; Triznawasti Y. Daik (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
This study aims to analyze the factors contributing to errors in writing poems on the theme "My Ambitions" (Cita-Citaku) within the Indonesian language subject for Grade III students at GMIT Pitungbang Elementary School, Northwest Alor District. The study employs a descriptive qualitative approach. The research subjects consisted of 19 Grade III students at GMIT Pitungbang Elementary School. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The research results indicate that the factors contributing to student errors in writing poems include internal factors: low reading interest, limited vocabulary, and a lack of motivation or self-confidence in self-expression. External factors include: teacher-centered instruction, a lack of engaging instructional media, and a lack of variety in writing techniques. Student errors in writing poems covered five aspects: (1) poem content—all students successfully completed the poem content based on the "My Ambitions" theme; (2) poem structure—17 out of 19 students correctly utilized rhyme, rhythm, and imagery; (3) language and style—16 students used effective language and appropriate writing styles; (4) creativity—16 students demonstrated good development of imagination and originality; and (5) neatness and completeness—15 students produced neat writing, while 4 students still made errors regarding punctuation and capitalization. Overall, 8 students (42%) fell into the low category for poetry writing proficiency, while 11 students (57%) fell into the moderate category. These errors stemmed from a lack of mastery regarding diction, weak imaginative skills, limited understanding of poetic structures and elements, and insufficient interest in reading and writing practice. Based on these findings, intensive guidance, creative and contextual teaching approaches, and the cultivation of regular habits for reading and writing poetry are required to optimally improve the students' poetry writing skills.